2019
DOI: 10.3389/fphys.2019.01224
|View full text |Cite
|
Sign up to set email alerts
|

QiDiTangShen Granules Activate Renal Nutrient-Sensing Associated Autophagy in db/db Mice

Abstract: QiDiTangShen granules (QDTS) have been proven to reduce the proteinuria in patients with diabetic nephropathy (DN) effectively. The present study was aimed to investigate the mechanism underlying QDTS’s renoprotection. The main components of QDTS were identified by ultra-high liquid chromatography-tandem mass spectrometry and pharmacological databases, among which active components were screened by oral bioavailability and drug-likeness. Their regulation on autophagy-related nutrient-sensing signal molecules (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…AMPK is another upstream regulator of mTOR, and it has been revealed that astragaloside IV (3, 6, and 12 mg/kg BW, daily, 8 weeks) could protect against albuminuria, glomerulosclerosis, and podocyte injury via AMPK α -mediated autophagy enhancement in STZ-induced DN mice 117 . Moreover, growing evidence has revealed that Sirtuin 1 (SIRT1) and HO-1 can promote autophagy through the activation of AMPK 118 , 124 , 153 . In a study, puerarin (5, 10, 20, and 40 mg/kg BW, daily, 12 weeks) was reported to protect podocytes from hyperglycaemia-induced injury through HO-1 and SIRT1-mediated upregulation of autophagy 124 .…”
Section: Mechanisms Involved In the Protective Effects Of Chinese Medicines Against Dnmentioning
confidence: 99%
“…AMPK is another upstream regulator of mTOR, and it has been revealed that astragaloside IV (3, 6, and 12 mg/kg BW, daily, 8 weeks) could protect against albuminuria, glomerulosclerosis, and podocyte injury via AMPK α -mediated autophagy enhancement in STZ-induced DN mice 117 . Moreover, growing evidence has revealed that Sirtuin 1 (SIRT1) and HO-1 can promote autophagy through the activation of AMPK 118 , 124 , 153 . In a study, puerarin (5, 10, 20, and 40 mg/kg BW, daily, 12 weeks) was reported to protect podocytes from hyperglycaemia-induced injury through HO-1 and SIRT1-mediated upregulation of autophagy 124 .…”
Section: Mechanisms Involved In the Protective Effects Of Chinese Medicines Against Dnmentioning
confidence: 99%
“…After obtaining the FLNC, the cluster module of isoseq3 is further used to cluster FLNC reads using hierarchical n*log(n) alignment and iterative cluster merging. In the novel variant isoform (NVI) calling step following pre-processing step described above, we utilized the collapse_isoforms_by_sam.py of cDNAcupcake [17], which takes bam file as input obtained by mapping cluster.fasta files to the pre-defined reference using minimap2 [18], to collapse two or more identical transcript isoforms into a unique transcript isoform. [Fig2A] Simultaneously, the number of full-length reads corresponding to different unique isoforms was also obtained, which are important supporting evidence for the called isoforms, and will be used as the parameter in the following filter step.…”
Section: Pipeline Overviewmentioning
confidence: 99%
“…Based on this principle, neoantigen-based immunotherapy has been developed by pharmaceutical companies or research institutions as a promising cancer treatment [4][5][6]. Additionally, novel proteins are also associated with other complex diseases, for instance, Alzheimer's [7], type II diabetes [8], liver disease [9][10][11][12][13][14], kidney disease [15][16][17][18][19][20], Obesity [21][22][23][24][25], and cardiovascular disease [26]. Therefore, effective identification of novel proteins is imperative for understanding human diseases and developing corresponding therapies.…”
Section: Introductionmentioning
confidence: 99%
“…R.J.Wang ( Gao et al, 2018 ). QDTS has been shown to be able to counteract kidney injuries and reduce proteinuria in DKD mice ( Wang et al, 2019 ). A study further investigated the mechanisms of action of QDTS and concluded that it could modulate the gut microbiota composition of db/db mice ( Wei et al, 2021 ).…”
Section: Herbal Medicine Gut-kidney Axis and Dkd/ckdmentioning
confidence: 99%